2014
DOI: 10.1038/ijir.2014.8
|View full text |Cite
|
Sign up to set email alerts
|

Personal factors that contribute to or impair women’s ability to achieve orgasm

Abstract: This work aims to identify factors that contribute and those that impair the ability to experience orgasm during sexual activity. It compared women (n=96) aged 18-61 (M=38.5 years) in a stable relationship that, after a normal arousal phase, do not have an orgasm (OD) with those that do (OA) regarding sociodemographic data, sexual frequency, talking about sex with their physician, talking about sex with their partner, sexual education, masturbation, sexual desire, sexual satisfaction, depression and anxiety. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…Regarding desire, Beck and Bozman (1995) found that subjective reports of anxiety decreased subjective reports of desire for both men and women. Similarly, de Lucena and Abdo (2014) found that increased levels of anxiety increased women's difficulty reaching orgasm. Finally, anxiety about pain may come from fear about experiencing pain during sexual activity, which might be due to a number of negative past experiences or a generally high sensitivity to pain (Basson, 2012).…”
Section: Sexual Dysfunction and Anxietymentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding desire, Beck and Bozman (1995) found that subjective reports of anxiety decreased subjective reports of desire for both men and women. Similarly, de Lucena and Abdo (2014) found that increased levels of anxiety increased women's difficulty reaching orgasm. Finally, anxiety about pain may come from fear about experiencing pain during sexual activity, which might be due to a number of negative past experiences or a generally high sensitivity to pain (Basson, 2012).…”
Section: Sexual Dysfunction and Anxietymentioning
confidence: 96%
“…Bradford andMeston (2006, p. 1068) describe state anxiety as "an acute emotional response characterized by subjective feelings of apprehension" and trait anxiety as "a stable measure that reflects an individual's dispositional tendency to experience state anxiety." Erectile dysfunction (ED) (Laurent & Simons, 2009;McCabe & Connaughton, 2014), premature ejaculation (PE) (McCabe & Connaughton, 2014), vaginismus (Watts & Nettle, 2010), female orgasm disorder (de Lucena & Abdo, 2014;Graham, 2010), and dyspareunia (Schnatz, Whitehurst, & O'Sullivan, 2010) have been found to either be exacerbated or maintained when a person has higher levels of state anxiety or anxiety sensitivity but less often for people with trait anxiety. The experience of anxiety affects four domains of sexual dysfunction arousal, pain, desire, and orgasm, and effects how therapist may treat a dysfunction (Laurent & Simons, 2009).…”
Section: Sexual Dysfunction and Anxietymentioning
confidence: 98%
“…This contraction of the vagina muscles and lack of adequate moisture in female makes it extremely difficult for them to engage in vaginal ingestion, which causes severe pain, lack of orgasm, and failure in sexual function. This defeat for female means sexual incompetence and makes it possible to avoid sexual intercourse in order to avoid this painful experience that can become a permanent cycle (Bigras, Daspe, Godbout, Briere, & Sabourin, 2017;Lin, Huang, & Chu, 2017); (Bigras, Godbout, & Briere, 2015;Bradford & Meston, 2006;Brassard, Dupuy, Bergeron, & Shaver, 2015;De Lucena & Abdo, 2014;Purdon & Watson, 2011;Van Minnen & Kampman, 2000;Watts & Nettle, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Se ha descrito que existen factores interpersonales, intrapersonales y socioculturales que influencian la percepción subjetiva del orgasmo en las mujeres (7,8), también se ha descrito que la disfunción orgásmica afecta la salud y calidad de vida de las mujeres (9,10). Los problemas para alcanzar el orgasmo se encuentran clasificados en el Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) como una disfunción sexual que requiere tratamiento (11), y se han propuesto estrategias de manejo psicológico (12) y ginecoló-gico de las disfunciones orgásmicas femeninas (13).…”
Section: Introductionunclassified